2004
DOI: 10.1016/s0377-2217(03)00163-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally biased weight determination in personnel selection

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 35 publications
0
18
0
6
Order By: Relevance
“…Ma and Li [25] studied the preferences between alternatives by fuzzy systems. Jessop [26] determined seven criteria from an overview of a job description: written communication, oral communication, planning, organising ability, team player, decisiveness, and working independently. Griffeth et al [27] identified the causes of turnovers in a company by examining the sources of employee turnover.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma and Li [25] studied the preferences between alternatives by fuzzy systems. Jessop [26] determined seven criteria from an overview of a job description: written communication, oral communication, planning, organising ability, team player, decisiveness, and working independently. Griffeth et al [27] identified the causes of turnovers in a company by examining the sources of employee turnover.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Afshari et al (2010) used simple additive weighting (SAW) approach in personnel selection problem. Jessop (2004) anticipated the minimally biased weight method with a view to helping decision makers in staff selection issue. Kousalya et al (2006) used AHP to rank alternatives like counseling, infrastructure, making lecture more attractive etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analytic hierarchy process (AHP) has been used widely for determining weights of indices in ecological assessment studies (Ye and Wu, 2000;. Despite its popularity and simplicity in concept, this method is often criticized for its inability to adequately incorporate the inherent uncertainty and imprecision associated with quantifying decision maker's perceptions using discrete values (Jessop, 2004;Bhuvadol et al, 2008;Dagdeviren and Yuksel, 2008). Based on the concept of fuzzy set theory, fuzzy AHP was originally introduced by Van Laarhoven and Pedrycz (1983).…”
Section: Weight Of Index Systemmentioning
confidence: 99%